Assessing the George W. Bush presidency : a tale of two terms - Wroe, Andrew; Herbert, Jon (Edinburgh University Press, 2009)
In one of the first volumes assessing the full two terms of the George W. Bush presidency, Wroe and Herbert have gathered the work of leading American and European scholars. In fifteen succinct and incisive chapters, authorities such as Jim Pfiffner, John Maltese, Graham Wilson and Alan Gitelson offer assessments of the Bush administration's successes and failures. Extensive attention is paid to Bush's foreign policy, including 'The War on Terror' but the focus is broadened to absorb not only the Bush Doctrine and its repercussions, but also his trade and homeland security policies. The president's domestic leadership in economics and social policy is investigated, as are his dealings as president with the other institutions of the U.S. political system. The result is a comprehensive guide to the Bush presidency and its legacy. Key Features Chapters by leading authorities from both sides of the Atlantic One of the first volumes to take into account the full span of the Bush presidency Broad-ranging coverage of both domestic and foreign policy Short, direct chapters providing incisive analysis of the administration's successes and failures